ҚӘНИГЕЛИК ТӘЛИМДЕ ЭТНОМӘДЕНИЙ КОМПЕТЕНЦИЯЛАРДЫ ҚӘЛИПЛЕСТИРИЎДЕ ПЕДАГОГИКАЛЫҚ ТИЙКАРЛАР - Губенова, Г.Т. (SCIENCE and SOCIETY, 2022)
The article is devoted to the effectiveness of the formation and development of ethnocultural competence among university students. Due to the fact that modern society has increased attention to the problem of forming a comprehensively developed, spiritually rich and creative, and most importantly tolerant students. Therefore, the educational process must be based on the creation of the foundations for the effective formation and development of the ethnocultural competence of the individual.